Persepektif Zikir Di Kalangan Sufi - Faisal Muhammad Nur (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2017)
Zikr is one of the methods used by the Sufi scholars to revive the soul from death spirit. A heart that does not remember the grace of Allah is considered dead by the Sufis. Remembrance can make a person aware of the existence of his true God. The method of remembrance is not limited to one aspect of life, but may be remembrance in various aspects of life as the essence of zikr is witnessing the existence of Allah SWT. Remembrance of Allah may be done silently in the heart, loudly on the tongue or even in one’s physical actions in a group or alone. In addition, there is no concrete verse or proposition that prohibits remembrance in various ways but advises Muslim to remembrance in various aspects of life